The effect of postpartum nursing guidance on early pelvic floor dysfunction recovery in women of advanced maternal age: a randomized controlled trial - Huang, Qingyu; Tang, Junfang; Zeng, Dingyuan; Zhang, Yu; Ying, Ting (Frontiers in Medicine, 2024)
Objective This study aimed to investigate the efficacy of postpartum nursing guidance in the treatment of early pelvic floor dysfunction (PFD) in women of advanced maternal age. Methods A total of 146 patients of advanced maternal age admitted to our hospital between January and December 2021 were enrolled in this study and randomly divided into two groups: the control group and the experimental group, with 73 patients in each group. Parturients in the control group received routine pelvic floor rehabilitation treatment, whereas those in the experimental group were given individualized postpartum nursing guidance alongside routine pelvic floor rehabilitation treatment. The recovery of pelvic floor muscle (PFM) strength, the incidence of PFD diseases and nursing satisfaction were compared between the two groups after 3 months of treatment. Results The enhancement of PFM strength in the experimental group significantly surpassed that in the control group. Furthermore, the experimental group exhibited a notably lower overall occurrence of PFD and significantly greater maternal satisfaction compared with the control group, and the difference was statistically significant (p < 0.05). Conclusion Combining postpartum nursing guidance with pelvic floor rehabilitation for women of advanced maternal age represents a treatment regimen deserving of clinical endorsement, as it offers numerous advantages, including substantial improvement in PFM strength, decreased incidence of PFD and enhanced patient satisfaction.